FORMATION OF NATIVE AMERICAN WRITTEN LITERARY TRADITION - Oksana G. Shostak (Вісник університету ім. А. Нобеля. Серія Філологічні науки, 2021)
Article deals with the attempt to describe the creating of Native American and First Nations of Canada written literature. The aim of our study is to characterize the phenomenon of the literary struggle for Indian independence as a historically determined phenomenon of cultural, literary and historical process in North America, in the context of cultural and literary search and transformations of Native American identities that take place in the context of indigenous peoples' adaptation to white expansion on the continent during the eighteenth and twenty-first centuries. In the article we used such methods as: historical-literary and historical-cultural methods as well as elements of structural analysis. The research deals with the ways of actualizing one of the most powerful concepts of the modern world – that of ethnicity, which stands out as a constituent of the basic Native American identity concept originated in the late 20th – early 21st centuries. The relevance of the research is determined by the importance of conducting more profound study of the concept that went through the objective stages of conceptualization and got fixed in the Indigenous Studies. Identity is manifested as a subjective feeling of belonging to a particular social group and at the same time it is a source of inspiration and continuity of each individual. The existence of the identity phenomenon is caused by the social context and the inviolability of social ties in society. The study of the North American identity has been and remains a problem with inexhaustible potential for researchers up to now. Identity becomes a form of literary discourse, causing self-discovery, self-interpretation, and the opportunity to transform into the “other” in one`s own country. Native American identity can be presented as a theory of social proximity and distance or as an interpretive scheme of gradual and direct discovery of oneself and the surrounding social reality through literature and social network communication. Anyhow interpretation of indigenous identity must be largely determined by a set of political, philosophical, historical, cultural, religious, ethnic concepts that dominate in given circumstances, determining the originality of indigenous identity in these circumstances. Today makes us witness a progressive development of American Indian identity in both cultural and civilizational and psychological dimensions through literary texts. The focus of the research is on the manifestations of the Indigenous national identity as a modern interdisciplinary phenomenon and the analysis of its projections in fiction. Theoretical and methodological foundations for understanding national identity in philosophy, culture, history, literary studies are determined, the ways of modeling national identity in contemporary Native American literature are traced. There are three dominant criteria of identity in such literary works: indigenous identity as a collective or personal feeling, manifestation or form of social consciousness, a social or individual-psychological phenomenon; fundamental identity as a doctrine, ideology or worldview, a systematized view of the world within a certain set of cultural and religious concepts; fundamental identity as a political movement, a political program based on ideology, doctrine or convictions.